Integrating Ecolinguistics into English Language Teaching: Opportunities and Challenges in Climate-Vulnerable Higher Education Contexts of Bangladesh - Md. Ahad Hossain; Farhana Yeasmin; Md. Zihad Hossen (ETERNAL (English Teaching Journal), 2026)
Ecolinguistics has generated growing theoretical interest in applied linguistics, yet empirical accounts of how teachers in climate-vulnerable, Global South contexts perceive and enact ecologically informed pedagogy remain scarce, with most existing literature drawn from Western and East Asian settings. This qualitative case study addresses that gap by examining how English language teachers in Khulna, Bangladesh, a coastal city bordering the Sundarbans mangrove forest. perceive the opportunities, constraints, and pedagogical value of integrating ecolinguistic perspectives into tertiary English Language Teaching (ELT). Guided by three research questions concerning perceived opportunities, structural barriers, and educational value, the study drew on semi-structured interviews with 15 teachers, interviews and classroom observations involving 40 students, and document analysis across four institutions, analyzed through Braun and Clarke’s reflexive thematic analysis. Findings revealed four interrelated themes: teachers held largely positive but operationally partial understandings of ecolinguistics; exam-oriented curricula, scarce materials, and limited training constituted the principal barriers to integration; locally grounded ecological issues, particularly the Sundarbans, salinity, and cyclones, generated marked learner engagement; and participants favored incremental, resource-based implementation over curricular overhaul. The study argues that ecolinguistic pedagogy in Khulna is constrained not by teacher resistance but by institutional and curricular unresponsiveness, offering implications for materials design, teacher training, and place-based language curricula in similarly vulnerable Global South contexts.